Challenges in Viscera Analysis: Addressing Errors in Forensic Reporting and Their Medico-Legal Implications (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Death is defined as the permanent and irreversible cessation of all biological functions that  sustain life. In cases of unnatural death, such as poisoning, an inquiry is conducted by the  police or magistrate under Indian law, followed by a post-mortem examination. Poisoning,  particularly in suicides, is a common cause of unnatural deaths encountered during autopsies.  The cause of death in such cases is confirmed only after receiving a chemical analysis report  from the Forensic Science Laboratory (FSL). Viscera samples are sent for chemical analysis  in suspicious death cases or when the cause of death is unclear after autopsy. Often, viscera  reports return negative, making it difficult for forensic doctors to determine the exact cause of  death, thereby delaying justice or, in some cases, weakening prosecution efforts. This article  explores the reasons for errors in viscera reports and discusses their medico-legal  implications.
Keywords: Death; Autopsy; Inquest; Viscera Report